A new paradigm for macroeconomic policy. (10th April 2011) - Arestis, Philip; Sawyer, Malcolm
In this paper we advocate a way of approaching macroeconomic policy, which stands in contrast to the now discredited 'new consensus in macroeconomics' policy framework. The five pillars of our approach are: the need for budget deficits to support the level of aggregate demand; full consideration of income distribution and its implications for the level of demand; the interest rate policy pursued by the central bank should aim for a constant real rate of interest with that interest rate broadly in line with the rate of growth; the coordination of economic policies with the implication of an end of central bank independence; and the key policy objective of the central bank should be financial stability.